2009
DOI: 10.2105/ajph.2009.161380
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of People Undergoing Foreclosure in the Philadelphia Region

Abstract: Objectives. We assessed the health status of people undergoing mortgage foreclosure in the Philadelphia region to determine if there was a relationship between foreclosure and health. Methods. Participants were recruited in partnership with a mortgage counseling agency. Participants' health status and health care use were compared with a community sample from the 2008 Southeastern Pennsylvania Household Health Survey. We used publicly filed foreclosure records to assess response bias. Results. Of the 250 peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(154 citation statements)
references
References 18 publications
9
143
1
1
Order By: Relevance
“…Second, as in all crosssectional studies, reverse causality may occur, and in fact, some authors suggest that poor health is one of the causes of foreclosure. 6 However, some longitudinal studies show greater risk of poor health among individuals with a history of foreclosure or housing instability. 13,14 A recent systematic review on foreclosure and health found only two studies based on individual-level data, which accounted for this potential bias by adjusting for baseline (pre-foreclosure) comorbidity.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, as in all crosssectional studies, reverse causality may occur, and in fact, some authors suggest that poor health is one of the causes of foreclosure. 6 However, some longitudinal studies show greater risk of poor health among individuals with a history of foreclosure or housing instability. 13,14 A recent systematic review on foreclosure and health found only two studies based on individual-level data, which accounted for this potential bias by adjusting for baseline (pre-foreclosure) comorbidity.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…[2][3][4] In two successive studies, Pollack et al found that people who were more than 2 months behind on their mortgage payments or who were involved in a foreclosure judgment had a higher prevalence of psychiatric disorders such as depression, anxiety, or dysphoria compared to people without housing instability. 5,6 Houle 7 recently reported that an increase in the rate of mortgage foreclosures at county level was associated with poorer mental health after adjusting for individual and contextual variables, while Fowler et al suggested that housing loss is associated with increased suicide risk. 8 Foreclosure has also been reported to have physical health effects, including higher rates of hypertension and heart disease compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is often society's poorest who are at greatest risk of adverse financial events because, having the least financial buffers, they are most vulnerable to the consequences of economic downturns (cf. Pollack & Lynch, 2009)…”
Section: Socio-economic Contextmentioning
confidence: 99%
“…These findings contribute to a growing literature which suggests that already-vulnerable populations are at increased risk for housing instability during periods of economic recession. 19,51 Second, housing instability was measured by asking participants whether they or a member of their household experienced housing instability due to the recession. Some participants classified as "lost housing" or "trouble paying the rent/ mortgage" may thus not have experienced housing instability themselves.…”
Section: Types Of Alcohol Problems By Perceived Family Supportmentioning
confidence: 99%